MARKETING MIX 7P DIBALIK SUKSESI KREATIF BISNIS KULINER BERTEMA ETNIK SEOUL PALACE SEMARANG (7P-Marketing Mix Behind The Creative Succession of Culinary Business with Ethnic Theme in Seoul Palace Semarang) - Heni Krisnatalia (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2021)
This study aims to determine the effect of 7P-Marketing Mix Elements (Product, Price, Place, Promotion, People, Process, and Physical Evidence) on the